Sequencing of novel agents in relapsed/refractory B‐cell acute lymphoblastic leukemia: Blinatumomab and inotuzumab ozogamicin may have comparable efficacy as first or second novel agent therapy in relapsed/refractory acute lymphoblastic leukemia. Issue 7 (1st December 2020) - Badar, Talha; Szabo, Aniko; Dinner, Shira; Liedtke, Michaela; Burkart, Madelyn; Shallis, Rory M.; Yurkiewicz, Ilana R.; Kuo, Eric; Khan, Muhammad Ali; Balasubramanian, Suresh; Yang, Jay; Hefazi, Mehrdad; et al.
Abstract : Background: The availability of novel agents (NAs), including blinatumomab and inotuzumab ozogamicin (InO), has improved the outcomes of patients with relapsed/refractory (RR) B‐cell acute lymphoblastic leukemia (ALL). Because of the relative effectiveness, it is often a challenge for clinicians to determine how to best sequence these NAs with respect to efficacy and toxicity. Methods: In this multicenter, retrospective study of patients with RR ALL treated with blinatumomab, InO, or both, their efficacy as a first or second NA was compared. Results: Among 276 patients, 221 and 55 received blinatumomab and InO, respectively, as a first NA therapy. The complete remission (CR)/complete remission with incomplete count recovery (CRi) rate was 65% and 67% for the blinatumomab and InO groups, respectively ( P = .73). The rate of treatment discontinuation due to adverse events was 4% and 7% in the blinatumomab and InO groups, respectively. Ninety‐two patients (43%) in the blinatumomab group and 13 patients (29%) in the InO group proceeded with allogeneic hematopoietic stem cell transplantation. The median overall survival (OS) was 15 and 11.6 months in the blinatumomab and InO groups, respectively. A subset analysis was performed for 61 patients who received both NAs (blinatumomab and then InO [n = 40] or InO and then blinatumomab [n = 21]). The CR/CRi rate was 58% for patients who received InO as the second NA and 52% for patients who received blinatumomab as the second NA. The median OS was 10.5 for patients who received InO as the second NA and 5.9 months for patients who received blinatumomab as the second NA ( P = .09). Conclusions: Although the limited power of this study to detect a significant difference between subgroups is acknowledged, the data suggest that blinatumomab and InO may have comparable efficacy as a first or second NA therapy in RR ALL. Abstract : Blinatumomab and inotuzumab ozogamicin have comparable efficacy as a first or second novel agent therapy in relapsed/refractory acute lymphoblastic leukemia. The sequencing of these novel agents should be tailored according to individual patient needs.